Answer:
7
x
−
1
y
=
5
Explanation:
First, we can write the equation in point-slope form. The point-slope formula states:
(
y
−
y
1
)
=
m
(
x
−
x
1
)
Where
m is the slope and (
x
1 y
1
)
is a point the line passes through.
Substituting the values from the problem gives:
(
y
−
2
)
=
7
(
x
−
1
)
Now, we need to convert to standard form. The standard form of a linear equation is:
A
x
+
B
y
=
C
where, if at all possible, A
, B
, and C are integers, and A is non-negative, and, A, B, and C have no common factors other than 1
We convert as follows:
y
−
2
=
(
7
×
x
)
−
(
7
×
1
)
y
−
2
=
7
x
−
7
−
7
x
+
y
−
2
+
2
=
−
7
x
+
7
x
−
7
+
2
−
7
x
+
y
−
0
=
0
−
5
−
7
x
+
y
=
−
5
−
1
(
−
7
x
+
y
)
=
−
1
×
−
5
(
−
1
×
−
7
x
)
+
(
−
1
×
y
)
=
5
7
x
−
1
y
=
5